Understanding the relationship between sexual harassment and eating disorder psychopathology: A systematic review and meta‐analysis. Issue 5 (10th March 2021) - Hayes, Samantha; Linardon, Jake; Kim, Christina; Mitchison, Deborah
Abstract: Objective: The experience of sexual harassment (SH) may exacerbate the drive toward an ideal and often unattainable physical appearance, creating the foundation of unhealthy eating, and greater shape and weight concerns. This systematic review aimed to synthesize evidence on the relationship between SH and eating disorder psychopathology, as well as mediating and moderating factors that contribute to this relationship. Method: Six key databases were searched from inception to August 2020; including CINAHL, PsycInfo, PubMed, Medline, Scopus, and Web of Science. Results: Overall, 15 studies meeting inclusion criteria were found, with 14 reporting a statistically significant relationship between SH and eating disorder psychopathology. A meta‐analysis with 12 cross‐sectional studies confirmed a small but significant effect for this concurrent association. Moderators of this relationship included gender, posttraumatic stress, and anxiety. No studies in this review conducted true mediation. Discussion: Conclusions about causal and mediating relationship between SH and eating disorder psychopathology are constrained by the preponderance of cross‐sectional design (14 of the 15 studies). Therefore, it is recommended that future studies focus on the use of longitudinal design, and also on adolescent populations, where first experiences of SH are usually reported, and which is also the peak age of onset for eating disorders. Resumen: Objetivo: La experiencia del acoso sexual puede exacerbar el impulso hacia una apariencia física ideal y a menudo inalcanzable, creando la base de una alimentación poco saludable, y mayores preocupaciones con la figura y peso corporal. Esta revisión sistemática tuvo como objetivo sintetizar la evidencia sobre la relación entre el acoso sexual y la psicopatología del trastorno alimentario, así como mediar y moderar los factores que contribuyen a esta relación. Método: Se buscó en seis bases de datos clave, desde el inicio hasta agosto de 2020; incluyendo CINAHL, PsycInfo, PubMed, Medline, Scopus, Web of Science. Resultados: En total, se encontraron 15 estudios que cumplían con los criterios de inclusión, y 14 reportaron una relación estadísticamente significativa entre el acoso sexual y la psicopatología de trastornos de la conducta alimentaria. Un metanálisis con 12 estudios transversales confirmó un pequeño pero significativo efecto para esta asociación simultánea. Los moderadores de esta relación incluyeron género, estrés postraumático y ansiedad. Ningún estudio en esta revisión llevó a cabo una verdadera mediación. Discusión: Las conclusiones sobre la relación causal y mediadora entre el acoso sexual y la psicopatología de los trastornos de la conducta alimentaria están limitadas por la preponderancia del diseño transversal (14 de los 15 estudios). Por lo tanto, se recomienda que los futuros estudios se centren en el uso del diseño longitudinal, y también en las poblaciones adolescentes, donde por lo general se reportan las primeras experiencias de acoso sexual, y que también son la edad pico de inicio para los trastornos de la conducta alimentaria.